Inverted dual U slot loaded truncated microstrip patch antenna for wireless applications - Thandapani, Kavitha; Subramani, Shiyamala (International Journal of Engineering and Technology, 2018)
Dual U Slot Loaded Truncated Microstrip Patch Antenna is designed for wireless applications. The proposed geometry comprised of two inverted U slots in truncated circular patch antenna operation covering 2.24 to 2.72 GHZ frequency bands are obtained. It is found that the slot and truncated is used to improve the bandwidth and return loss respectively. The resonant frequency is found to be 2.5GHZ. The bandwidth of the proposed antenna for lower and upper resonant frequency is found to be 19.2%. The proposed antenna is fed by 50â„¦ co-axial probe feed and simulated on Rogers RT/duroid5880 substrate.Â Rogers RT/duroid 5880 substrate has dielectric constant and loss tangent of 2.2 and 0.0009 respectively. An air gap is used in this proposed design for tuning the desired frequencies and increasing the bandwidth. The antenna shows an acceptable gain of 2.1dB to 5.7dB with unidirectional pattern over the obtained frequency band.Â